Risk management committee, ownership structure and financial performance - Sharifah Nabihah, Syed Yasin (2017)
The role of risk management committee (RMC) under the corporate governance consist of monitoring the risk strategies, policies and risk tolerance level as well as reviewing the sufficiency of risk management policies and framework. Risk management committee performs a very important function in the monitoring of the risk and internal control. Thus, the main objective of the study is to examine the effect of the existence of risk management committee on firm performance of companies listed in the Main Market of Bursa Malaysia. In addition, the study also examines the effect of ownership structure of director and family ownership on firm performance. ROA and ROE are used as proxy to measure the firm performance. Sample of the study is based on 20% companies in each industry excluding finance companies. Data were collected from 154companies in the financial year 2015.The study uses agency theory to predict the relationship. Descriptive analysis shows that only 18% of the sample companies have stand-alone risk management committee and 28% of the sample companies have joining risk management committee with other committees such as audit committee. The mean of family ownership is 21.93% and the mean of director ownership is 36.81%. The regression analysis revealed that there is no significant relationship between the existence of risk management committee, family ownership and director ownership with firm performance. In addition, the result indicates that only board composition, the control variable has significant negative relationship with firm performance.